Salmonella enterica Serovar Typhimurium ompS1 and ompS2 Mutants Are Attenuated for Virulence in Mice - Rodríguez-Morales, Olivia (American Society for Microbiology, 2006)
Salmonella enterica serovar Typhimurium mutants with mutations in the ompS1 and ompS2 genes, which code for quiescent porins, were nevertheless highly attenuated for virulence in a mouse model, indicating a role in pathogenesis. Similarly, a strain with a mutation in the gene coding for LeuO, a positive regulator of ompS2, was also attenuated.